A column perfusion test to assess the kinetics of nutrient release by soluble, sparingly soluble and coated granular fertilizers. Issue 5 (27th June 2019) - Baird, Roslyn; da Silva, Rodrigo C.; Degryse, Fien; McLaughlin, Michael J.
Abstract: In recent years, innovations in fertilizer research have principally been in the design of products to supply more timely plant nutrients and mitigate detrimental losses to the environment. In the development of these fertilizers, a laboratory method to comparatively screen a large number of formulations for the rate of nutrient release is a critical first step in formulation optimization to significantly reduce time spent on pot and field trials, reducing costs considerably. Currently, given the absence of a standard laboratory method for all fertilizers, adaptions of a method for coated fertilizers from the International Organization for Standardization (2017) ISO 21263 and other column tests are being used which are often complex and/or require manual sampling which can be laborious, time consuming and costly. The method presented here evaluates the dynamic release in real time by continuously perfusing samples in columns utilizing an automated sample accumulation system for short‐term and long‐term release studies and eliminates the need for soil/sand packing of columns. Mass balance is accounted for by analysing the residue after dissolution and the amount released is expressed as a % of the total nutrient content in the product. This method is reliable, uncomplicated and cost‐effective and has been used to test uncoated soluble fertilizers, nanofertilizers, fertilizers with newly developed coating technologies and other slowly soluble fertilizers, to assess the effect of variables like coating chemistry and thickness, fertilizer composition or fertilizer particle size on release rate.